2016
DOI: 10.2147/ijn.s103994
|View full text |Cite
|
Sign up to set email alerts
|

Efficient intravesical therapy of bladder cancer with cationic doxorubicin nanoassemblies

Abstract: Nanoparticles have promising applications in drug delivery for cancer therapy. Herein, we prepared cationic 1,2-dioleoyl-3-trimethylammonium propane/methoxypoly (ethyleneglycol) (DPP) nanoparticles to deliver doxorubicin (Dox) for intravesical therapy of bladder cancer. The DPP micelles have a mean dynamic diameter of 18.65 nm and a mean zeta potential of +19.6 mV. The DPP micelles could prolong the residence of Dox in the bladder, enhance the penetration of Dox into the bladder wall, and improve cellular upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Collectively, the obtained data indicate a slight cardiotoxic effect of Doxorubicin during its intravesical administration, which, in general, correlates with the literature data describing the clinical efficacy of this method of administration [6]. However, in our opinion, for a more detailed assessment of the state of the myocardium, it is necessary to further investigate the dynamics of changes in the electrophysiological activity of the heart, as well as biochemical markers of its damage.…”
Section: Discussionsupporting
confidence: 84%
“…Collectively, the obtained data indicate a slight cardiotoxic effect of Doxorubicin during its intravesical administration, which, in general, correlates with the literature data describing the clinical efficacy of this method of administration [6]. However, in our opinion, for a more detailed assessment of the state of the myocardium, it is necessary to further investigate the dynamics of changes in the electrophysiological activity of the heart, as well as biochemical markers of its damage.…”
Section: Discussionsupporting
confidence: 84%
“…Another study load epirubicin with poly(ethyl-2-cyanoacrylate)(PECA) NPs and demonstrated that this system could provide sustained drug tissue concentrations and significant cytotoxicity in human BC cells [ 67 ]. Jin et al encapsulated doxorubicin (Dox) with another cationic nanoparticle and significantly improved the efficiency of Dox in orthotopic BC model [ 68 ].…”
Section: Bladder Cancer Treatment and Nanotechnologymentioning
confidence: 99%
“…5-FU, DOX and EPI with a broad antineoplastic spectrum are used to treat many different types of cancer as colon or rectum, breast, liver, bladder and brain [ 50 , 61 , 79 , 80 ]. The main drawbacks of direct chemotherapy with these agents can be listed as severe depression of hematopoiesis (anemia, leucopenia, thrombopenia), infection and cardiotoxicity regarding EPI [ 50 ], 5-FU resistance and rapid clearance from the body [ 6 ] and DOX cumulative cardiotoxicity and nephrotoxicity [ 82 ]. Overall, these severe side effects had a deep impact on the mortality rate of cancer patients [ 83 ].…”
Section: State Of the Artmentioning
confidence: 99%